miRNA-mRNA crosstalk in porcine longissimus dorsi muscle: multi-omics identification of breed-specific regulatory networks and functional verification - Li, Xiaojin; Xie, Fei; Jiang, Changsheng; Jin, Mengmeng; Zhao, Weigang; Ghonaim, Ahmed H.; Ren, Man; Li, Shenghe; Gao, Yafei; Yin, Zongjun (Frontiers in Animal Science, 2025)
Intramuscular fat (IMF) deposition is a key determinant of meat quality, and microRNAs (miRNAs) have emerged as important regulators of this process. However, studies investigating how miRNAs influence IMF deposition and muscle growth in the longissimus dorsi (LD) tissues of Chinese and Western pig breeds remain limited. In this study, we analyzed the LD tissues of Huoshou black (HS) pigs and Yorkshire (YY) pigs using transcriptome sequencing, identifying 2,833 differentially expressed genes (DEGs) and 51 differentially expressed miRNAs (DEMs). Functional enrichment analysis demonstrated that the DEGs were significantly associated with metabolic pathways related to IMF deposition and fatty acid synthesis, including the MAPK and AMPK signaling pathways and the fatty acid biosynthesis pathway. Target genes of the DEMs were enriched in metabolic pathways such as PI3K–Akt signaling, apelin signaling, and the biosynthesis of unsaturated fatty acids. Four randomly selected DEGs and four DEMs were validated using quantitative real-time PCR (qRT-PCR), confirming the reliability of the sequencing data. Furthermore, candidate miRNAs associated with muscle growth and IMF deposition (miR-10a-5p, miR-29b, miR-29a-3p, miR-122-5p, miR-194a-5p, miR-221-3p, miR-31, miR-127, and miR-205) were identified through the construction of an miRNA–mRNA interaction network. The interaction between MYH7B and miR-205 was further validated using a dual-luciferase reporter assay. Overall, this study provides novel insights into miRNA-mediated regulation of IMF in LD muscle between Chinese and Western pig breeds, offering a theoretical foundation for future strategies to improve pork quality.